2023
DOI: 10.3390/app13042179
|View full text |Cite
|
Sign up to set email alerts
|

Time Evolution of the Modulus of Elasticity of Metakaolin-Based Geopolymer

Abstract: The objective of the research is to develop a new family of geopolymeric materials and to use an experimental methodology to characterize the mechanical behavior of the materials obtained by alkaline activation of metakaolin using a compound activator. The researchers also intend to study the unknown time evolution of the modulus of elasticity and the influence of the composition of the aggregates on the strength of the material. Like the material’s strength, the results have a direct influence on structural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Indeed, the maximum strength was probably reached before that point. Considering the deformation of the material, which was equivalent to that attained on the 28th day of curing for an OPC-based concrete, Lopes et al [69] have shown that metakaolin-based geopolymers reach maturity around day 15 or 16 of curing. Furthermore, and as stated above, increasing the curing temperature by a limited amount helps to reduce this time interval without reducing the final strength.…”
Section: Effect Of Curing Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the maximum strength was probably reached before that point. Considering the deformation of the material, which was equivalent to that attained on the 28th day of curing for an OPC-based concrete, Lopes et al [69] have shown that metakaolin-based geopolymers reach maturity around day 15 or 16 of curing. Furthermore, and as stated above, increasing the curing temperature by a limited amount helps to reduce this time interval without reducing the final strength.…”
Section: Effect Of Curing Temperaturementioning
confidence: 99%
“…The remaining diagrams were derived (only) from the point in gray, assuming a given value of the modulus of elasticity (MOE). In this regard, it is worth adding that the presented MOE values have a scientific basis: (i) for the MKW geopolymer, MOE = 12 GPa, as determined by Lopes [71]; (ii) for the MKB geopolymer, MOE = 18 GPa, as determined by Lopes [69]; (iii) the EC2 [39] was used to estimate the expected value for the OPC mortar given the compressive strength (MOE = 41 GPa).…”
Section: Tensile Stress-strain Diagrammentioning
confidence: 99%